Traditional Uses, Chemical Constituents, Biological Properties, Clinical Settings, and Toxicities of Abelmoschus manihot L.: A Comprehensive Review - Luan, Fei; Wu, Qianhong; Yang, Yan; Lv, Haizhen; Liu, Daoheng; Gan, Zhaoping; Zeng, Nan (Frontiers in Pharmacology, 2020)
Abelmoschus manihot, as an annual herbal flowering plant, were widely distributed throughout Eastern Europe and in temperate and subtropical of Asia. Its flowers have been traditionally used for the treatment of chronic kidney disease (CKD) in China. Currently, more than 128 phytochemical ingredients have been obtained and identified from flowers, seeds, stems, and leaves of A. manihot, and the primary components are flavonoids, amino acids, nucleosides, polysaccharides, organic acids, steroids, and volatile oils, etc. A. manihot and its bioactive constituents possess a plethora of biological properties, including anti-diabetic nephropathy, antioxidant, antiadipogenic, anti-inflammatory, analgesic, anticonvulsant, antidepressant, antiviral, anti-tumor, cardioprotective, anti-platelet, neuroprotective, immunomodulatory, hepatoprotective activities, and effect on cerebral infarction and bone loss effects, etc. However, insufficient utilization and excessive waste has already leaded to rapid reduction of the resources, and the study on sustainable use of A. manihot is urgent and necessary. Moreover, the major biologically active constituents and the mechanisms of action of the flower have yet to be elucidated. The present paper provides an advance and comprehensive review of the traditional uses, chemical constituents, pharmacological activities, pharmaceutical, quality control, toxicological, and clinical settings to emphasize the foregrounds of this plant, and lays a solid foundation for further development of A. manihot.